Critical appraisal of cardiac implantable electronic devices: complications and management - Padeletti L (Dove Medical Press, 2011)
Luigi Padeletti1, Giosuè Mascioli2, Alessandro Paoletti Perini1, Gino Grifoni1, Laura Perrotta1, Procolo Marchese3, Luca Bontempi3, Antonio Curnis31Istituto di Clinica Medica e Cardiologia, Università degli Studi di Firenze, Italia; 2Elettrofisiologia, Istituto Humanitas Gavazzeni, Bergamo, Italia; 3Elettrofisiologia, Spedali Civili, Brescia, ItaliaAbstract: Population aging and broader indications for the implant of cardiac implantable electronic devices (CIEDs) are the main reasons for the continuous increase in the use of pacemakers (PMs), implantable cardioverter-defibrillators (ICDs) and devices for cardiac resynchronization therapy (CRT-P, CRT-D). The growing burden of comorbidities in CIED patients, the greater complexity of the devices, and the increased duration of procedures have led to an augmented risk of infections, which is out of proportion to the increase in implantation rate. CIED infections are an ominous condition, which often implies the necessity of hospitalization and carries an augmented risk of in-hospital death. Their clinical presentation may be either at pocket or at endocardial level, but they can also manifest themselves with lone bacteremia. The management of these infections requires the complete removal of the device and subsequent, specific, antibiotic therapy. CIED failures are monitored by competent public authorities, that require physicians to alert them to any failures, and that suggest the opportune strategies for their management. Although the replacement of all potentially affected devices is often suggested, common practice indicates the replacement of only a minority of devices, as close follow-up of the patients involved may be a safer strategy. Implantation of a PM or an ICD may cause problems in the patients' psychosocial adaptation and quality of life, and may contribute to the development of affective disorders. Clinicians are usually unaware of the psychosocial impact of implanted PMs and ICDs. The main difference between PM and ICD patients is the latter's dramatic experience of receiving a shock. Technological improvements and new clinical evidences may help reduce the total burden of shocks. A specific supporting team, providing psychosocial help, may contribute to improving patient quality of life.Keywords: pacemaker, cardiac cardioverter-defibrillator, cardiac implantable electronic devices, infection, recall, quality of life